ევროპისა და ე.წ. „სხვის“ ანტიკური მოდელები - ნადარეიშვილი, ქეთევან (ლოგოსი, 2023)
Given the suggestion that Europe comprises the succession of its various representations made in different places, the study of Europe’s first representation - ancient Europe and its surrounding world -- is especially topical in current research about European identity. Consequently, the investigation of how early Europeans viewed foreign peoples and how they differentiated themselves from them, and how the so- called other helped construct their identity, acquires a major importance. The article studies the main models of so-called other of the first representator of Europe – the Greeks, namely, the main dimensions of the images of the Persians and Egyptians as represented by the Greek authors; investigates the role of historical context and geopolitics in constructing the core elements of the first xenostereotypes; analyses the similarities existed in the opposition Europe: non-Europe of the ancient and the subsequent periods of the European history. The article will suggest useful insights concerning the extent of the influence the ancient models of the other had on the images of foreign peoples created by Europeans in the middles ages and the modern periods as well as concerning the role that ancient theories played in self-identification of Europe and understanding of Europe’ role in a global context.